2018
DOI: 10.1200/jco.2017.77.0305
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Programmed Death–1 Pathway Inhibitors Among Patients With Non–Small-Cell Lung Cancer and Preexisting Autoimmune Disorders

Abstract: Purpose Although programmed death (PD)-1 pathway inhibitors are now used in nearly all patients with advanced non-small-cell lung cancer (NSCLC), the large number of patients with NSCLC and concurrent autoimmune disease (AID) have been universally excluded from immunotherapy clinical trials. Therefore, the safety of PD-1 and PD-ligand 1 (PD-L1) inhibitors in patients with NSCLC and underlying AID is currently unknown. Methods As part of a multi-institutional effort, we retrospectively collected clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
299
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(324 citation statements)
references
References 16 publications
22
299
2
1
Order By: Relevance
“…First, the authors suggested classifying preexisting autoimmune diseases according to systems in order to assess if rheumatic disorders were more likely to flare with ICIs. Such trends have been reported in other studies , with the limitation that the highest percentage of preexisting autoimmune diseases in the cohorts studied were rheumatic disorders (n = 27 [52%] in ref. 1 and n = 25 [45%] in ref.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…First, the authors suggested classifying preexisting autoimmune diseases according to systems in order to assess if rheumatic disorders were more likely to flare with ICIs. Such trends have been reported in other studies , with the limitation that the highest percentage of preexisting autoimmune diseases in the cohorts studied were rheumatic disorders (n = 27 [52%] in ref. 1 and n = 25 [45%] in ref.…”
supporting
confidence: 85%
“…For these reasons, we consider it more meaningful to classify the diseases according to the diagnosis, with a larger sample size, even if a classification by system might add clinical value. Interestingly, more flares were reported in the psoriasis group in our cohort, and 50% of patients with inflammatory bowel disease (IBD) experienced a flare, compared to lower flare frequencies reported in other retrospective cohorts . IBD represented a larger sample size in our cohort.…”
mentioning
confidence: 56%
“…In our study, the incidence of irAEs of any grade and G3/G4 irAEs among patients with pre‐existing AIDs were 65.9% and 9.4%, respectively. The rates of irAEs of any grade seem worse than those observed by Menzies et al (29%), Leonardi et al (38%), and Danlos et al (44.4%), although G3/G4 events are quite comparable (10% of G3, and 10.7%, respectively—not reported by Danlos et al) . Forty patients (47.1%) among those with pre‐existing AIDs developed a flare of the underlying disease; similarly, in the studies of Leonardi et al (23%) and Danlos et al (24.4%), the flare rates were lower than the incidence of irAEs overall, whereas in the study of Menzies et al, it was higher (38%) than the “conventional” irAEs rate.…”
Section: Discussionmentioning
confidence: 67%
“…A history of autoimmunity has previously been thought to confer a higher risk of toxicity to PD‐1 inhibitors; therefore, patients with such a history have been excluded from clinical trials with these drugs. Existing retrospective data suggests that PD‐1 inhibitors can safely be used in patients with a history of AD and although flares of the pre‐existing AD are common, they are often of mild severity and manageable . Four patients (8%) in the present cohort had a history of pre‐existent AD, and three of these four patients experienced either a flare of their underlying AD or another IrAE with PD‐1 inhibitor therapy.…”
Section: Discussionmentioning
confidence: 82%